Mechanism of visible-light-driven photocatalytic degradation of endosulfan pesticide by gold nanoparticles. (21st July 2020) - Goel, Puja; Arora, Manju
Abstract: Spherical shaped gold nanoparticles (GNPs) of size around ∼9 nm were successfully used for photocatalytic degradation of hazardous endosulfan (ES) pesticide. GNPs absorb sunlight at ambient condition in aqueous medium to enhance localized surface plasmon resonance (LSPR) which initiate hydrolysis, oxidation and reduction chemical reactions for the mineralization of ES molecules. Infrared transmittance spectra of GNPs treated ES solutions revealed formation of amorphous carbon and hydrocarbon as final reaction products indicating the nearly complete mineralization of ES as evidenced from their TEM images also. The disappearance of chloro carbon and sulphite functional groups peaks of ES in IR transmittance spectra confirmed their degradation. TEM images also support the optical absorption spectra consisting of inter-band and LSPR bands pertaining to individual and clustered GNPs ensembles. The redshift in LSPR absorption peak positions along minor and major axis of clustered GNPs ensembles is attributed to the change in GNPs polarizability on interaction with the electric component of visible light. The chemical reaction pathway for ES molecule degradation by the photocatalytic GNPs has been proposed in the light of inferences drawn from TEM images, IR transmittance and optical absorption spectra.